The Vital@Work Study. The systematic development of a lifestyle intervention to improve older workers' vitality and the design of a randomised controlled trial evaluating this intervention - van der Beek Allard J; Proper Karin I; Strijk Jorien E; van Mechelen Willem (BMC, 2009)
Abstract Background A major contributor of early exit from work is a decline in health with increasing age. As healthy lifestyle choices contribute to better health outcomes, an intervention aimed at an improved lifestyle is considered a potentially effective tool to keep older workers healthy and vital, and thereby to prolong labour participation. Methods Using the Intervention Mapping (IM) protocol, a lifestyle intervention was developed based on information obtained from 1) literature, 2) a short lifestyle questionnaire aimed at indentifying the lifestyle behaviours among the target group, and 3) focusgroup (FG) interviews among 36 older workers (aged 45+ years) aimed at identifying: a) key determinants of lifestyle behaviour, b) a definition of vitality, and c) ideas about how vitality can be improved by lifestyle. The main lifestyle problems identified were: insufficient levels of physical activity and insufficient intake of fruit and vegetables. Using information from both literature and FG interviews, vitality consists of a mental and a physical component. The interviewees suggested to improve the mental component of vitality by means of relaxation exercises (e.g. yoga); physical vitality could be improved by aerobic endurance exercise and strength training. The lifestyle intervention (6 months) consists of three visits to a Personal Vitality Coach (PVC) combined with a Vitality Exercise Programme (VEP). The VEP consists of: 1) once a week a guided yoga group session aimed at relaxation exercises, 2) once a week a guided aerobic workout group session aimed at improving aerobic fitness and increasing muscle strength, and 3) older workers will be asked to perform once a week for at least 45 minutes vigorous physical activity without face-to-face instructions (e.g. fitness). Moreover, free fruit will be offered at the group sessions of the VEP. The lifestyle intervention will be evaluated in a RCT among older workers of two major academic hospitals in the Netherlands. At baseline, after 6 and 12 months, measurements (primary: lifestyle and vitality, and secondary: work-engagement and productivity) will take place. Discussion The lifestyle programme is developed specifically tailored to the needs of the older workers and which is aimed at improving their vitality. Trial registration NTR1240